Is there frequency-specificity in the motor control of walking? The putative differential role of alpha and beta oscillations - Charalambous, Charalambos C.; Hadjipapas, Avgis (Frontiers in Systems Neuroscience, 2022)
Alpha and beta oscillations have been assessed thoroughly during walking due to their potential role as proxies of the corticoreticulospinal tract (CReST) and corticospinal tract (CST), respectively. Given that damage to a descending tract after stroke can cause walking deficits, detailed knowledge of how these oscillations mechanistically contribute to walking could be utilized in strategies for post-stroke locomotor recovery. In this review, the goal was to summarize, synthesize, and discuss the existing evidence on the potential differential role of these oscillations on the motor descending drive, the effect of transcranial alternate current stimulation (tACS) on neurotypical and post-stroke walking, and to discuss remaining gaps in knowledge, future directions, and methodological considerations. Electrophysiological studies of corticomuscular, intermuscular and intramuscular coherence during walking clearly demonstrate that beta oscillations are predominantly present in the dorsiflexors during the swing phase and may be absent post-stroke. The role of alpha oscillations however, has not been pinpointed as clearly. We concluded that both animal and human studies should focus on the electrophysiological characterization of alpha oscillations and their relation to the CReST. Another approach in elucidating the role of these oscillations is to modulate them and then quantify the impact on walking behavior. This is possible through tACS, whose beneficial effect on walking behavior (including boosting of beta oscillations in intramuscular coherence) has been recently demonstrated in both neurotypical adults and stroke patients. However, these studies still do not allow for specific roles of alpha and beta oscillations to be delineated because the tACS frequency used was much lower (i.e., individualized calculated gait frequency was used). Thus, we identify a main gap in the literature, which is tACS studies actually stimulating at alpha and beta frequencies during walking. Overall, we conclude that for beta oscillations there is a clear connection to descending drive in the corticospinal tract. The precise relationship between alpha oscillations and CReST remains elusive due to the gaps in the literature identified here. However, better understanding the role of alpha (and beta) oscillations in the motor control of walking can be used to progress and develop rehabilitation strategies for promoting locomotor recovery.